Comparison of unilateral spinal anesthesia and L1 paravertebral block combined with psoas compartment and sciatic nerve block in patients to undergo partial hip prosthesis - Demirel, I.; Ozer, A. B.; Duzgol, O.; Bayar, M. K.; Karakurt, L.; Erhan, O. L. (Verduci Publisher, 2014)
OBJECTIVES: Just as hip prosthesis, most of the patients undergoing orthopedic lower extremity surgery (OLES) belong to the advanced age group. Sciatic nerve block combined with psoas compartment block is used as a technique alternative to central neuraxial block and GA. In geriatric patients that will undergo partial hip prosthesis, the effects of the methods of unilateral spinal anesthesia (SA) and L1 paravertebral block combined with psoas compartment block (PCB) and sciatic nerve block (PCSL) on peroperative hemodynamic parameters and the duration of need for postoperative analgesia were studied. PATIENTS AND METHODS: Fifty patients from the ASA III-IV group were randomly divided into two groups. Group SA was administered spinal anesthesia with hyperbaric bupivacaine (2 ml, 0.5%) from the selected intervertebral distance (L4-L5 or L3-L4) in lateral position. Group PCSL was administered L1 paravertebral block combined with PCB and sciatic nerve block with bupivacaine hydrochloride (total 35 ml). Hemodynamic parameters (HR: heart rate and MAP: mean artery pressure) were recorded in pre- and post-intervention 5-minute intervals. The initial time of the need for analgesia of patients were evaluated postoperatively. RESULTS: Any failure in methods implemented on patients in either group was not observed. Times of anesthesia and surgical preparation of patients were observed to have significantly prolonged in the PCSL compared to Group SA (p < 0.005). Hundred and 5th and 110th min. mean arterial pressures of patients was found to be significantly higher in Group SA compared to Group PCSL (p < 0.05). The initial time of the need for analgesia was observed to be significantly prolonged in Group PCSL (432.80 +/- 236.77 min) compared to Group SA (185.40 +/- 171.40 min) (p < 0.001). CONCLUSIONS: Unilateral SA conducted with bupivacaine hydrochloride and PCSL block technique provided a hemodynamically similar activity in the perioperative period in patients that underwent partial hip operation. However, PCSL block implementation extended the initial time of the need for analgesia in postoperative period. PCSL method could be selected in cases belonging to such group of patients. PCSL block can be a alternative anesthetic tecniques in patients that underwent partial hip operation.
Keywords: Partial hip prosthesis; Unilateral spinal anesthesia; Lumbar plexus block; Sciatic nerve block; Hemodynamic effects